Setting Distance Relay Pada Jaringan Transmisi 150 kV Sistem Gorontalo - Taufiq Ismail Yusuf; Laode Muh. Taslan (Jurnal Teknik, 2018)
Disturbance on the transmission line can cause disruption of normal flow of a stream, in the transmission line of the most common disorders are short circuit. Distance relay are used as security for the transmission line because of its ability to quickly eliminate interference. In this research, symmetrical components method is used in to analyzing the single-phase short circuit current and two phase – ground in SUTT 150 kV Gorontalo Transmission System. The results were obtained, single-phase short circuit at most 1098,11 Ampere and the smallest is 497,67 Ampere and two phase – ground at most = 1026,91 Ampere and = 650,86 and the smallest is = 442,63 Ampere and = 337,55 Ampere, while the calculation results setting distance relay it is appropriate to avoid the reach selectivity setting exceeding 80% and avoid looping and time settings on zona1 = 0 s zona2 = 0,4 s and zona3 = 0,8 s according to the impedance value of the secondary 1 < 2 as well as on 2 < 3.